Academic Writing – Guidelines for a Term Paper, Bachelor and Master Thesis - Müller, Stefanie; Roth, Angela (2015)

A Case About the Diffusion of Co-Creation Expertise in Organizations - Krämer, Katja; Roth, Angela; Möslein, Kathrin (ISPIM Dublin, 2014)
WiSo-Import:2015-04-17:5304

Actor integration in service systems – exploring effects on a micro level - Jonas, Julia; Roth, Angela; Möslein, Kathrin (The 2015 Naples Forum on Service, 2015)

Actors’ Roles in Citizen-driven Innovation - Sengewald, Timon; Roth, Angela (ISPIM Connects Osaka – Connecting and Empowering Society, 2024)
Amidst the global polycrisis, municipalities are urged to boost their resilience, with innovation playing a pivotal role in responding to challenges. Citizen-driven innovation has proven effective during the COVID-19 pandemic, with numerous solutions emerging from civic hackathons. However, while open innovation in businesses is well-researched, the dynamics of social and citizen- driven innovation remain less understood. Engaging civil society actors can advance municipal innovation and mitigate crises. This study, using a multiple case study approach with a qualitative content analysis of interviews and other available materials, aims to enhance our understanding of coordinating citizen- driven innovation and the interplay of different actor roles. By understanding the roles of actors and the unique aspects of social and public open innovation, municipalities can unlock the full potential of their citizens. This research offers insights to help cities harness the power of citizen-driven innovation more effectively.<br
Keywords: public open innovation; citizen-driven innovation; innovation actor roles

A Framework for the Assessment of Collaborative Competences in Servitizing Firms - Posselt, Tim; Roth, Angela (R&D Management 2013, 2013)
WiSo-Import:2015-04-17:4946

Analyse von Anforderungen in der Logistikbranche - Erste Implikationen für die Berufsbildung - Roth, Angela (Zeitschrift für Berufs- und Wirtschaftspädagogik, 2012)
WiSo-Import:2015-03-26:4233

Approaches for Enhancing Productivity of Networked Service Delivery: A Review and Assessment - Daiberl, Christofer; Roth, Angela; Möslein, Kathrin (26th Annual RESER Conference, 2016)

A Systematic Assessment of Empirical Research in Success Factors in New Service Development - Posselt, Tim; Roth, Angela; Förstl, Kai (EURAM, 2012)
WiSo-Import:2015-04-17:4272

A Systematic Characterization of Artificial Intelligence Business Models as a Fundament for Business Model Innovation and Strategic Decision-Making - Wilga, Matthäus; Jalowski, Max; Kirschbaum, Julius; Roth, Angela (21st European Academy of Management (EURAM) Conference 2021, 2021)

Aufgabentransfer — Möglichkeiten und Grenzen - Roth, Angela (Neue Wege in der Automobillogistik, 2007)

Bildungsmarkt Logistik - Ausbildung, Weiterbildung, Studium für Logistik und Supply Chain Management. - Roth, Angela; Klaus, Peter (DVV Verlag, 2008)
WiSo-Import:2015-04-13:2041

Boost Or Bust: Characterizing Value Co-Creation With AI-Based Non-Human Agents From A User Perspective - Wilga, Matthäus; Lugmair, Nina; Schymanietz, Martin; Roth, Angela (13th SERVSIG Conference, 2024)

Bringing interactive hybrid value creation to downtown retailers - towards a service-manufactory - Roth, Angela; Möslein, Kathrin; Jonas, Julia (Cambridge Service Week, 2014)

Change of Organizational Ambidexterity in Corporate Venture Units: how an Innovation Unit Increasingly Develops Exploitative Tendencies - Seilz, Veronika; Krause-Söhner, Elena; Schaller, Christian; Roth, Angela (HMD : Praxis der Wirtschaftsinformatik, 2023)
The ability to engage in organizational ambidexterity (OA), i.e., to simultaneously make innovative efforts (exploration) in addition to optimizing the existing business (exploitation), is crucial for the long-term success of companies. Separate corporate venture units (CVUs) are often founded for this purpose. They have a special role to play as they have to contribute to the ambidexterity of their parent companies and at the same time develop their own OA-configurations, i.e. combinations of exploration and exploitation. Previous research shows that these combinations change over time and that exploitation is increasing in originally explorative innovation units. However, there has been little insight into how the associated changes look like, what initiates them, and how they can be influenced. This study therefore addresses the following research question: Through what can exploitative and explorative tendencies develop in a CVU? Using a case study in a CVU of the paper processing industry, various examples can be used to show how the combinations of exploration and exploitation change over time at different levels and how these changes are influenced by the CVU and its members. Concluding management implications indicate that accompanying role changes and the individual attitudes of employees need to be guided by management. <br
Keywords: Ambidexterity; Innovation capability; Corporate venture unit; Dynamic perspective; Multi-level construct; Case study

Characterising smart service systems – Revealing the smart value - Kurtz, Julian; Zinke-Wehlmann, Christian; Lugmair, Nina; Schymanietz, Martin; Roth, Angela (Journal of Service Management Research, 2023)
The increasing use of digital technologies is creating new values, which can be unfold in smart service systems (SSS). Although SSS offer multiple values in products and services, research is still struggling to fully capture the specific values of" smart" as result of digital technologies. Therefore, there is no all-encompassing value understanding of SSS. In our work, we derive values of SSS, especially the" smart" values, by a qualitative analysis of cases in an open coding approach. These cases are identified by a systematic literature review. The derived “smart” values are eg increasing system transparency and autonomy, increasing knowledge integration, and enabling ecological savings fostering value in context. The specific values of" smart" in SSS give rise to value in context as a representation of those specific values. In addition, the emergence of derived values in SSS is further illustrated with an SSS value continuum, which presents value in product, value in services, and value in context as characterisation of values in SSS. The derived values and the SSS value continuum developed are intended to promote a better understanding of SSS and its value manifestations, and provide a basis for further research into SSS as a theoretical lens for value co-creation.<br

Characterizing the Roles of AI-Enabled Non-Human Agents in Service Systems - Wilga, Matthäus; Hajjam, Layla; Lugmair, Nina; Schymanietz, Martin; Roth, Angela (19th International Conference on Wirtschaftsinformatik, 2024)
Machines are becoming more versed at adapting to environmental impulses and their operational contexts, changing their roles in service systems. These machines can autonomously fulfill goals within defined boundaries set by legal actors and thereby exhibit agency. As interactions are at the core of services, the integration of such non-human agents into value co-creation has the potential to heavily impact the innovation of services. Following a four-step type construction approach based on empirical open-source data on 130 services, we develop a multi-dimensional characterization of six roles that non-human agents fulfill in service systems. Taking a systemic perspective, we identify service system interactions involving non-human agents and how their contributions impact value propositions. Our findings forward the understanding of service processes involving non-human agents and their impact on value co-creation, benefiting both theory and practice through knowledge on the engineering of service systems and value-driven, user-centered human-machine interaction

Co-Creating Innovation in Service Systems - Exploring the Effects of Cross-Disciplinary Problem Solving - Jonas, Julia; Roth, Angela; Möslein, Kathrin (2015 EurOMA Conference, 2015)

Co-Creating Service Innovation in Interdependent Service Systems - Jonas, Julia; Roth, Angela; Möslein, Kathrin (Forum on Markets & Marketing Karlstad, 2014)
WiSo-Import:2015-04-17:5305

Combining open innovation and knowledge management for a community of practice-an analytics driven approach - Dinter, Barbara; Kollwitz, Christoph; Möslein, Kathrin; Roth, Angela (Proceedings of the Twenty-second Americas Conference on Information Systems, 2016)

Complexity and interdependencies of actor integration for service innovation in service systems? Insights from the exploration of micro level practices - Jonas, Julia; Roth, Angela; Möslein, Kathrin (5th Formum on markets and marketing FMM 2016, 2016)

Conceptualizing productivity within a service network: The case of JOSEPHS® - Daiberl, Christofer; Roth, Angela; Möslein, Kathrin (Euroma Konferenz, 2016)

Das Versprechen nachhaltiger digitaler Dienstleistungen - eine Fallstudie - Ries, Lena; Lugmair, Nina; Kurtz, Julian; Beckmann, Markus; Roth, Angela (Sustainable Service Management, Forum Dienstleistungsmanagement, 2024)

Data as Curse or Blessing. Business Model Innovation from the Perspective of System Dynamics - Förster, Matthias; Bansemir, Bastian; Roth, Angela (European Academy of Management (EURAM) Conference 2018, 2018)
Digital data is becoming an increasingly important part for the development of innovative business models. Nevertheless, there is great uncertainty among companies about how data affects the business model. To answer this question this paper examines the role of data and identifies essential data relations inside business models. A system dynamic perspective is chosen to facilitate a sufficient understanding of the data relations that drive the business model behaviour. An exploratory multiple case study was used to examine 33 innovative business model cases that have been generated through a hackathon. The qualitative data collection took place based on several data sources: artefacts of the hackathon, team observations as well as semi-structured interviews. The study shows that business enabling data relations are dynamic nature and evolve over time as the business model itself unfolds in its implementation. Depending on data contexts, dependencies and relations, data can have positive business fostering effects or a destructive effect on the entire business model. In other words, data can be a curse or blessing for a business mode
Keywords: Business Model Innovation; Value Realization from Data

Decoding the context of servitization: socio-technical pivots on the journey to service-oriented business models in manufacturing firms - Kurtz, Julian; Meyer, Patrick; Roth, Angela (Production Planning & Control, 2023)
Servitization has been discussed in academia and practice for decades, but there is still a lack of concrete guidance for manufacturing firms to orchestrate their servitization journeys. This study addresses this deficiency by analysing 88 annual reports of manufacturing firms. Using a multi-cycle inductive coding approach, six pivotal factors in servitization journeys were derived in order to decode their context. The pivotal factors represent fields of action in which manufacturing firms are currently active on their servitization journeys. They include both frontstage (e.g. market proposition) and backstage (e.g. process excellence) factors and predominantly emphasise technological over social activities. This exploratory study contributes to a more nuanced and contextualised understanding of the transformation of manufacturers into service-oriented firms. More importantly, this study sheds new light on servitization research by applying a socio-technical perspective and proposes a practical structuring of the servitization journey with tandems to navigate the journey.<br
Keywords: Servitization; business model innovation; product-service systems; socio-technical system perspective

Der Kunde als Mitentwickler - Herausforderungen für die marktorientierte Führung - Roth, Angela; Möslein, Kathrin; Reichwald, Ralf (Marketing Weiterdenken. Zukunftspfade für eine marktorientierte Unternehmensführung, 2018)

Der Logistikbildungsmarkt 2020 - Bedarfsgerechte Bildungsangebote für die Logistikwirtschaft der Zukunft (Habilitationsschrift) - Roth, Angela (2010)
WiSo-Import:2015-04-13:2155
Keywords: Logistikbildungsmarkt; Zukunft Logistik; Kompetenzen Logistik; Kompetenzen Logistik; Logistikbildungsmarkt; Zukunft Logistik

Design of a Method For Service Systems Engineering in the Digital Age - Höckmayr, Benedikt; Roth, Angela (Proceedings of the 38th Internationcal Conference on Information Systems (ICIS), 2017)

Design principles for establishing a multi-sided open innovation platform: lessons learned from an action research study in the medical technology industry - Daiberl, Christofer; Oks, Sascha Julian; Roth, Angela; Möslein, Kathrin; Alter, Steven (Electronic Markets, 2019)
Innovation in the medical technology (med tech) industry has a major impact on well-being in society. Open innovation has the potential to accelerate the development of new or improved healthcare solutions. Building on work system theory (WST), this paper explores how a multi-sided open innovation platform can systematically be established in a German med tech industry cluster in situations where firms had no prior experience with this approach. We aim to uncover problems that may arise and identify opportunities for overcoming them. We performed an action research study in which we implemented and evaluated a multi-sided web-based open innovation platform in four real-world innovation challenges. Analyzing the four different challenges fostered a deeper understanding of the conceptual and organizational aspects of establishing the multi-sided open innovation platform as part of a larger work system. Reflecting on the findings, we developed five design principles that shall support the establishment of multi-sided open innovation platforms in other contexts. Thus, this paper contributes to both theory and practic
Keywords: Multi-sided platforms; Open innovation; Work system theory; Medical technology industry cluster; Action research

Developing new services for e-mobility: An integrated inline-offline co-creation approach - Daiberl, Christofer; Höckmayr, Benedikt; Roth, Angela; Möslein, Kathrin (innteract 2016, 2016)

Development of a classification framework for technology based retail services: a retailers’ perspective - Wolpert, Stefan; Roth, Angela (International Review of Retail, Distribution and Consumer Research, 2020)
The purpose of this study is to identify different types of technology-based retail services (TBRS) for brick and mortar environments and analyze them by developing a framework that can be used to classify TBRS in respect of their dimensions, categories and category elements. The research design is twofold. First, this study conducts a systematic literature review to identify a relevant body of various TBRS in scientific literature. Second, it uses grounded theory as a method to analyze the identified TBRS from part one, in order to expose TBRS classification dimensions for developing a classification framework. This study identified 35 TBRS from 124 peer-reviewed articles, published worldwide between 2003 and 2019. It shows that TBRS can be classified along four dimensions: (1) participant issues, (2) technology issues, (3) information issues, and (4) intended purposes. The findings indicate that the majority of TBRS has technology-generated customer contact and is a fixed in-store totem with a low task complexity. Most TBRS enhance customer experience or improve store management. This study addresses a significant and on-going change in retailing. It provides insights into the TBRS market and offers an analytical classification framework to take TBRS to pieces, showing their elements and purposes. The framework can both guide future research and aid retail practitioners in analyzing TBRS.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Digital transformation; retail technology; smart retailing; smart technology; technology based retail services

Dienstleistungsentwicklung im digitalen Kontext – ein Plattformansatz - Boukhris, Aida; Höckmayr, Benedikt; Genennig, Stefan; Roth, Angela (Digitale Dienstleistungsinnovationen, 2019)

Dienstleistungsentwicklung im offenen Innovationslabor - Ein Blick durch die Unternehmensbrille - Roth, Angela; Jonas, Julia (Service Business Development, 2018)

Dienstleistungswende zur Nachhaltigkeit - Böhmann, Tilo; Roth, Angela; Satzger, Gerhard; Kurtz, Christian; Lewandowski, Tom; Wilga, Matthäus; Hottum, Peter; Schemmer, Max (2023)

Die systematische Entwicklung von Servicesystemen im digitalen Zeitalter – Ein Fakten-basierter Ansatz - Höckmayr, Benedikt; Roth, Angela; Genenning, Stefan M.; Boukhris, Aida; Möslein, Kathrin; Kalb, Dominik; Arnhold, Dennis; Hohmann, Christoph; Posselt, Tim; Danzinger, Frank; Eckert, Albert; Mittelstädt, Sebastian (Dienstleistungsinnovationen durch Digitalisierung - Geschäftsmodelle – Methoden – Umsetzungsbeispiele, 2020)
Die Gestaltung von bzw. die aktive Vernetzung in Servicesystemen werden zunehmend als wesentliche Erfolgsfaktoren für Unternehmen gesehen. Gleichzeitig können im digitalen Zeitalter aufgrund einer Vielzahl von in Maschinen verbauter Sensoren große Datenmengen generiert werden. Hierdurch können neue digitalisierte Servicesysteme entwickelt und durch smarte Dienstleistungen für die Kunden neue Wertekonstellationen geschaffen werden. Allerdings müssen die beteiligten Akteure, insbesondere KMU, hierfür befähigt werden, gemeinschaftlich smarte Dienstleistungen entwickeln, einzuführen und betreiben zu können. Der vorliegende Beitrag beschäftigt sich mit dieser Thematik und stellt eine im Rahmen des Forschungsprojektes „Smarte Dienstleistungsfabrik“ entwickelte und erprobte Methodik für ein solches Fakten-basiertes Service System Engineering sowie Erkenntnisse aus empirischen Erhebungen sowie drei konkrete Anwendungsfällen aus der Unternehmenspraxis vor.<br

Digitalisierung als Treiber für Faktenbasiertes Service-Systems-Engineering - Roth, Angela; Höckmayr, Benedikt; Möslein, Kathrin (Dienstleistungen 4.0 - Konzepte-Methoden-Instrumente. Band 1. Forum Dienstleistungsmanagement, 2017)

Digitization-enabled Innovation in Service Systems: An Empirical Analysis of the German MDAX Companies - Genennig, Stefan; Pauli, Tobias; Roth, Angela; Möslein, Kathrin (European Academy of Management (EURAM), 2018)

Digitization-Enabled Innovation in Sports - A Service Systems' Perspective on Professional Soccer Players - Genennig, Stefan; Schymanietz, Martin; Roth, Angela (European Academy of Management (EURAM) Conference 2019, 2019)

Driving Service Productivity of Open Innovation Labs - Daiberl, Christofer; Roth, Angela (Innovating in the Open Lab, 2020)

Employee perspectives on value realization from data within data-driven business models - Förster, Matthias; Bansemir, Bastian; Roth, Angela (Electronic Markets, 2022)
Firms are innovating data-driven business models (DDBMs) to realize value from data. Yet, making DDBMs work is challenging, and DDBMs often fall short of expected value realization. One reason for this shortfall is that firms do not know how employees, who decisively influence a DDBM’s value realization, view this complex and multi-facetted topic. We think it is necessary to understand the employees’ perspectives, the dimensions that build these perspectives and the characteristics employees are particularly interested in regarding value realization from data. We address this research gap by applying the Q-methodology to examine the perspectives among 70 employees across twelve DDBMs at a German automotive manufacturer. This yields eight perspectives, e.g., data advocacy, data caution or data practical. By exploring these perspectives, we provide a first groundwork on how employees view and appraise value realization from data which adds to the strive for mastering value realization from data within DDBMs.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Data-driven business models; Value realization from data

Enhancing Service Productivity: A Review of Approaches from a Service Network Perspective - Daiberl, Christofer; Roth, Angela; Möslein, Kathrin (Reser Conference, 2016)

Entwicklung digitaler Servicesysteme – Akteure, Ressourcen und Aktivitäten - Fritzsche, Albrecht; Jonas, Julia; Roth, Angela (Service Engineering - Von Dienstleistungen zu digitalen Service-Systemen, 2018)
Im Rahmen der digitalen Transformation entstehen vielerorts neue Wertschöpfungssysteme, die durch Vernetzung von Akteuren und Ressourcen über organisationale Grenzen hinweg hybride Angebote aus Produkten und Dienstleistungen auf den Markt bringen. Unter operativen Gesichtspunkten gilt die Aufmerksamkeit der Beteiligten dabei meist der Entwicklung spezieller Lösungen für konkrete Probleme. Weitere Entwicklungen hinsichtlich der Verteilung von Aufgaben und der Zuordnung von Verantwortlichkeiten erhalten dagegen wenig Aufmerksamkeit. Der hier vorliegende Beitrag nutzt Erkenntnisse aus verschiedenen Projekten im Kontext von Industrie 4.0, um eine übergreifende Sicht auf die Dynamiken der Entstehung digitaler Servicesysteme zu entwickeln. Die Projekte werden dazu im Hinblick auf die involvierten Akteure, Ressourcen und Aktivitäten analysiert. Um das große Ganze in komplexen Digitalisierungsprojekten betrachten zu können, werden folgende Lösungsstrategien abgeleitet: a) die Nutzung von Interaktionsräumen, b) das systemische Management durch Regelungscockpits und c) die Einbeziehung des gesamten Lebenszyklus eines Servicesystems.<br

Entwicklungspfade und Meilensteine moderner Logistik - Skizzen einer Roadmap - Prockl, Günter; Bauer, Angela; Pflaum, Alexander; et al. (Gabler, 2004)
WiSo-Import:2015-09-23:1853

Evolving crucial competences for a systematic service innovation process - A conceptual framework - Roth, Angela; Hofmann, Bettina (Reser Conference 2012, 2012)
WiSo-Import:2015-04-17:4256

Exploring Customers' Acceptance of and Resistance to Service Robots in Stationary Retail - a Mixed Method Approach - Meyer, Patrick; Jonas, Julia; Roth, Angela (ECIS 2020 Research Papers, 2020)
Stationary retailers continue to try to respond to customers’ needs with regard to service offering and quality. Consequently, they are attempting to develop innovative value propositions and co-create value with customers through new technologies. Among other technologies, service robots (SR) are said to have the potential to revitalise interactive value creation in stationary retail. Nonetheless, the integration of such technologies poses new challenges. Use cases are subject to research, but few studies have explored customers’ perceptions of SRs from a service systems’ perspective, though this is crucial to integrating SRs into stationary retail service systems. In this study, a mixed method approach is adopted to explore customers’ acceptance of and resistance to SRs. First, a qualitative exploratory interview study is conducted among 24 customers. Second, a qualitative survey and a quantitative questionnaire are carried out. The findings identify decisive drivers and barriers, i.a. ‘social presence’ and ‘role congruency’ and reveal i.a. that customers envision harmonious human-robot teams with transparent responsibilities that improve service interactions: while SRs assist frontline employees (FLE) and respond to simple customer inquiries, FLEs can dedicate more time engaging with customers and providing professional customer advice. Moreover, customers suggest that SRs be introduced gradually and with FLEs’ qualified assistance.<br
Keywords: service robots; service systems; customer interaction; human-robot interaction

Exploring the diffusion of co-creation expertise in organizations. - Krämer, Katja; Roth, Angela; Möslein, Kathrin (21st International Product Development Management Conference, 2014)

Forschungsergebnisse zur Transportsteuerung der Zukunft - Tourengebietsplanung und Tourenplanung - Bauer, Angela (Bundesverband Deutscher Postdienstleister (BvDP) – BvDP Arbeitskreis Verkehr, 2002)

From Tour Planning to Area Management: Tour Area Planning for Logistic Service Providers - Bauer, Angela; Feige, Dieter Manfred; Werr, Harald; Klaus, Peter (Sixth International Workshop on Distribution Logistics, 2001)

Frontline employees’ acceptance of and resistance to service robots in stationary retail - an exploratory interview study - Meyer, Patrick; Jonas, Julia; Roth, Angela (19th Conference of the European Academy of Management (EURAM), 2019)

Frontline Employees' Acceptance of and Resistance to Service Robots in Stationary Retail - An Exploratory Interview Study - Meyer, Patrick; Jonas, Julia; Roth, Angela (Journal of Service Management Research, 2020)

Gemeinsam unter Strom: Community-basierte Dienstleistungsinnovation für e-Mobility - Kollwitz, Christoph; Daiberl, Christofer; Dinter, Barbara; Roth, Angela; Möslein, Kathrin (2018)

How Digitization is Changing Technology Management for Service Innovation – an Integrated Method - Genennig, Stefan; Roth, Angela (RESER Conference, 2018)

How does the User Type Affect the Acceptance of Digital Innovation on the Job - Sengewald, Timon; Boha, Julian; Roth, Angela (Proceedings of the 2020 on Computers and People Research Conference, 2020)
Digital technologies promise greater effectiveness and higher productivity for companies. The question of the factors influencing the success of such technologies has long been a subject of research. However, these factors seem to be depending on the user type. This paper handles the case of the implementation of a new mobile application to support distinct work processes and presents preliminary results. A total of two field observations and 22 interviews were conducted to create a framework that promotes the development of digital innovations by systematically identifying characteristics that improve the adoption rate.<br

How Employees Perceive Planned Organizational Change: Insights from a Workspace Change Project in the German Insurance Industry - Breutner, Natalie; Roth, Angela (J APPL BEHAV SCI, 2024)
Based on a symbolic–interpretive and social–constructivist research approach, this longitudinal study explores how employees perceive workspace changes. Rich empirical processual data that were continuously collected during the change process were used to analyze workspace changes as a new type of organizational change, thereby contributing to sensemaking research. Three types of change recipients from employees’ responses to a workspace change based on differences in their underlying cognitive, behavioral, and affective patterns throughout the sensemaking process were identified: those with positive attitudes and perceptions, those with negative attitudes and perceptions, and those exhibiting a change toward positive attitudes and perceptions. As a practical contribution, change agents and leaders can gain insights and guidance for managing different employees by considering the individual patterns that trigger changes in employees’ perceptions throughout the change process. These insights about sensemaking also contribute to organizational development and change management research.
CRIS-Team Scopus Importer:2024-11-01
Keywords: affect; attitudes; change management; cognition/cognitive processes; organizational change; organizational development; sensemaking/sensegiving

Industrial Service Clouds: Entwicklung eines Kriterienkatalogs und Identifikation von Entwicklungsbedarfen - Posselt, Tim; Hohmann, Christoph; Boukhris, Aida; Genennig, Stefan; Höckmayr, Benedikt; Danzinger, Frank; Roth, Angela; Möslein, Kathrin (2018)

Initial Design of a Method for Service Systems Engineering in the Digital Age - Höckmayr, Benedikt; Roth, Angela; Möslein, Kathrin (17h European Academy of Management Conference (EURAM), 2017)

Innovating in the Open Lab - Fritzsche, Albrecht; Jonas, Julia; Roth, Angela; Möslein, Kathrin (De Gruyter Oldenbourg, 2020)
Keywords: Open Laboratories; Innovation Management; Service Innovation; Value Co-Creation; Innovation Platforms and Ecosystems

Innovation in Service Ecosystems: A role perspective - Roth, Angela; Jonas, Julia; Genennig, Stefan; Möslein, Kathrin (RESER annual conference, 2016)

Innovation KI-basierter Dienstleistungen für die industrielle Wertschöpfung – Ein artefaktzentrierter Ansatz - Jalowski, Max; Roth, Angela; Oks, Sascha Julian; Wilga, Matthäus (Künstliche Intelligenz im Dienstleistungsmanagement, 2021)
Dieser Beitrag zeigt auf, wie insbesondere für kleine und mittlere Unternehmen die Gestaltung und Innovation von KI-basierten Dienstleistungen in der industriellen Wertschöpfung unterstützt werden kann. Dazu werden Herausforderungen bei der Entwicklung KI-basierter Dienstleistungen erhoben und anschließend Artefakte präsentiert, die zur Innovation von Dienstleistungen zum Einsatz kommen. Diese werden basierend auf den zuvor identifizierten Herausforderungen adaptiert, um die Innovation von KI-basierten Dienstleistungen zu ermöglichen.<br

Innovation process design for servitisation: the digital service innovation case at uvex - Kurtz, Julian; Meyer, Patrick; Lugmair, Nina; Ries, Lena; Roth, Angela (Journal of Enterprise Information Management, 2025)
Purpose: The purpose of this study was to increase knowledge of digital service innovation in servitisation by extending design principles and proposing an innovation process design for smart product-service systems (PSS) development. Furthermore, the study addresses the alignment of multiple stakeholders in the development of smart PSS, thereby bridging the gap between theory and practice. Design/methodology/approach: A qualitative 17-month action design research approach was taken. This study designed an innovation process for smart PSS development. For this, different development streams were synchronised and multiple stakeholder perspectives were integrated. Drawing on the socio-technical systems perspective as theoretical lens, the authors utilised knowledge in the field of digital service innovation and servitisation. In multiple iterations, the authors, together with practitioners, explored how best to synchronise different smart PSS development activities to ensure subsequent operations of the system. Findings: The findings of the longitudinal study conducted with the manufacturing firm uvex propose a hybrid stage-gate innovation process design for smart PSS development. An evaluation with several international academics and practitioners enhances the rigour of the innovative approach. Originality/value: The findings contribute to the literature on digital service innovation and servitisation by applying a rarely used socio-technical perspective to innovation process design for smart PSS development. The longitudinal approach over 17 months in a qualitative action design research setting adds to the knowledge base with novel insights from practitioners’ problems.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Action design research; Digital service innovation; Innovation process design; Product-service systems; Servitization; Socio-technical systems

Innovation von datengetriebenen Geschäftsmodellen - Förster, Matthias; Bansemir, Bastian; Roth, Angela (HMD : Praxis der Wirtschaftsinformatik, 2021)
In the context of the ongoing digitalization, the competitiveness of companies is increasingly dependent on their ability to innovate data-driven business models. However, this poses major challenges for companies, and so, data-driven business models, once they have been implemented on the market, often fall short of expectations in terms of value realization, e.g. in the form of revenues or cost savings. In particular, this is due to the fact that value-realizing or value-reducing influencing factors often only become apparent after the implementation in the market. At this point, companies lack concrete procedure models to counter these influencing factors and to successfully implement data-driven business models and realize value. By means of a design science research approach, this study develops an interview- and workshop-based procedure model that enables practitioners to implement and realize value from data-driven business models. The application of the procedure model in five data-driven business models of a German premium car manufacturer has shown that it offers practitioners useful support. For example, it provides an easy-to-understand methodological approach that helps to identify and evaluate value-realizing and value-reducing influencing factors, promote cross-functional, shared knowledge on value realization, decision factors and the leveraging effects of different measures. Additionally, the assignment of limited company resources to the implementation of different measures in relation to their effects is considered.<br
Keywords: Data-driven business models; Procedure model for value realization; Innovation; Design science research

Integrierte Entwicklung smarter Produkt-Service-Systeme - Oks, Sascha Julian; Schymanietz, Martin; Jalowski, Max; Posselt, Tim; Roth, Angela (Smart Services, 2022)
Die Innovation von smarten Produkt-Service-Systemen (sPSS) bietet Unternehmen zahlreiche Potentiale, geht jedoch auch mit nicht zu vernachlässigenden Herausforderungen einher. Diese Studie erhebt den Status quo der Innovation von sPSS, sowohl mittels einer Umfrage unter Unternehmen als auch literaturbasiert, um anschließend acht Gestaltungsleitsätze für integrierte sPSS-Innovationsprozesse abzuleiten. Diese Gestaltungsleitsätze dienen als Grundlage der Gestaltung einer sPSS-Anwendungskarte, die Unternehmen bei der Bewältigung von Herausforderungen und dem Ausschöpfen der Potentiale von sPSS-Innovationen unterstütz

Interaktive Kunden als Herausforderung: Die Fallstudie „JOSEPHS® – Die Service-Manufaktur“ - Roth, Angela; Fritzsche, Albrecht; Jonas, Julia; Danzinger, Frank; Möslein, Kathrin (HMD : Praxis der Wirtschaftsinformatik, 2014)
WiSo-Import:2015-03-26:5299

Joseph’s - The Service Manufactory - Roth, Angela; Möslein, Kathrin; Jonas, Julia (Cambridge Service Week - Academic Conference, 2013)
WiSo-Import:2015-04-17:4947

Josephs - The Service Manufactory - Roth, Angela; Möslein, Kathrin; Jonas, Julia (Cambridge Service Week - Academic Conference Cambridge, 2013)

Key challenges in developing and implementing new workspace concepts. RESER annual conference (Gothenburg) - Roth, Natalie; Roth, Angela (RESER (The European Association for REsearch on SERvices) annual conference, 2018)

KI-Paradigmenwechsel der Wertschöpfung: Die Triade "Dienstleistung - Arbeit - KI" gestalten - Roth, Angela; Benz, Carina; Wilga, Matthäus; Satzger, Gerhard; Böhmann, Tilo; Hottum, Peter; Lewandowski, Tom (2023)

Kollaborative Gestaltung innovativer Mobilitätskonzepte - Rapp, Maximilian; Krämer, Katja; Roth, Angela; Schmitz-Dräger, Cathrin (6. Wissenschaftsforum Mobilität Duisburg - Proceedings, 2014)
WiSo-Import:2015-04-17:5310

Künstliche Intelligenz als Treiber für Dienstleistungsinnovation - Roth, Angela; Oks, Sascha Julian (Automatisierung und Personalisierung von Dienstleistungen, 2020)
Künstliche Intelligenz – KI – ist ein aktuell viel diskutiertes Thema, welches in vielen Anwendungskontexten eine Rolle spielt. In diesem Beitrag liegt der Fokus auf KI-initiierten und -basierten Innovationen im Dienstleistungskontext. Dazu werden Fragen eruiert, inwieweit sich die Potentiale der KI auf Dienstleistungsinnovationen auswirken, welche Stellhebel zur Gestaltung von KI-gestützten Dienstleistungen existieren, wie KI den Plattformgedanken bereichern kann und wie sich Organisationen dadurch verändern. Mit dem Fokus auf Dienstleistungssysteme werden darüber hinaus die bestehenden Wirkungszusammenhänge diskutiert und die Funktionen von KI als Nukleus, Enabler, Impuls, Grenzobjekt und Innovation zur Dienstleistungsentwicklung eingeführ

Lagermodellierung für logistische Netze - Das "modulare Knotenmodell" als Konzept zur dynamischen Abbildung von Lagern in Netzen (Dissertation) - Bauer, Angela (Deutscher Verkehrsverlag, 2002)

Laying the foundation for high performance of new digital logistics ventures - Schwemmer, Martin; Roth, Angela; Pflaum, Alexander (International Journal of Business and Systems Research, 2021)
New ventures can have a crucial effect to infuse innovation into an industry. The recent emergence of new logistics ventures can be identified as a relevant trend. Taking into account digitalisation, this study analyses, how new logistics ventures can lay the foundation for high performance in a digital environment at an early stage of existence. The chosen research approach combines secondary data collection and an interview study following the principles of grounded theory. The sample is composed of founders, investors, corporate investors and consultants from Central Europe experienced in the area of interest. As a result, ten propositions for new venture performance in a digitalising environment are presented and discussed. These propositions can be categorised in four dimensions: entrepreneurial team, entrepreneurial resources, entrepreneurial opportunity, and strategic and organisational fit. Likewise, these propositions constitute a shortlist of what is relevant to lay the foundation for high new digital logistics venture performance.<br
Keywords: logistics startups; new ventures; logistics; supply chain management; logistic entrepreneurship

Leitfaden zum wissenschaftlichen Arbeiten – Empfehlungen für Studenten der Betriebswirtschaftslehre, insbesondere der Logistik - Roth, Angela; Müller, Stefanie (2005)

Leitfaden zur Erstellung von Seminar-, Bachelor- und Masterarbeiten – Empfehlungen für Studenten der Betriebswirtschaftslehre - Roth, Angela; Müller, Stefanie (2011)

Making Sense of the Sustainable Smart PSS Value Proposition - Lugmair, Nina; Ries, Lena; Schymanietz, Martin; Beckmann, Markus; Roth, Angela (ICIS 2022 Proceedings.3., 2022)
While academia attributes superior value potential to sustainable smart PSS (SSPSS), in practice, they are not widely implemented. To address this gap, we analyze how the notion of SSPSS value is constructed through sensemaking. Adopting a case study approach, we explore differences in organizational sensemaking. Moreover, we analyze how the three functional roles “digital innovation and technology”, “sustainability”, and “market” involved in innovating SSPSS make sense of the value proposition. We conclude that value is subjective and the value proposition of SSPSS is multi-faceted. Each facet is constructed through the interaction of organizational, functional roles’, and individual sensemaking. At the organizational level, commitment, identity, and expectations influence the creation of shared meaning. At the functional role level, actors differ in their sensemaking based on the cognitive frames applied. At the individual level, subjective beliefs impact sensemaking. Hence, sensemaking is a multi-level process that raises the question of alignment.<br

Managing collaboration for servitization – A service ecosystems perspective - Lugmair, Nina; Posselt, Tim; Kurtz, Julian; Ries, Lena; Roth, Angela (33rd International RESER Conference 2023, 2024)

Managing New Workspace Concepts—A Strategic Change Project in a German Insurance Company - Roth, Natalie; Roth, Angela (British Academy of Management, 2019)

Managing the Dynamics of Ambidexterity: A longitudinal case study of the European Envelope-Industry - Krause, Elena; Roth, Angela; Schaller, Christian; Möslein, Kathrin (2019 R&D Management Conference, 2019)

Märkte, Anwendungsfelder und Technologien in der Logistik - Ergebnisse und Reflexion von 20 Jahren Logistikforschung - Müller, Stefanie; Roth, Angela; Schmidt, Norbert (Gabler, 2009)
WiSo-Import:2015-09-23:1983
Keywords: Logistikkonzepte; Logistikmarkt; Entwicklkung Logistik; Entwicklkung Logistik; Logistikkonzepte; Logistikmarkt

Microfoundations of Organizational Competence for Servitization - Posselt, Tim; Roth, Angela (Journal of Competences, Strategy & Management, 2017)

Modelling of Warehouses in logistical networks - Bauer, Angela (Doctoral Seminar CLM Conference, 2005)

Multifaceted and even contradictory? Impulses to push efficiency and innovativeness and the dynamic role of ambiguity in context of a German university - Krause-Söhner, Elena; Roth, Angela; Schaller, Christian (Journal of Business Research, 2022)
Organizations have to find ideal combinations of efficient and innovative practices to manage the dynamic in changing contexts. However, we know less so far about managing the occurring dynamics of exploration–exploitation change and how they can be influenced. This study develops a novel dynamic and multi-level view on organizational ambidexterity (OA; i.e. the capacity to explore and exploit simultaneously). This view builds upon a processual constructivist perspective and the context of strategic change in a German Multi-campus university. In a longitudinal in-depth case study, organizational dynamics are investigated at multiple levels and sites. The results show that diverse—and somehow contradictory—impulses are operating on multiple levels and these are interpreted in different ways, leading to several organizational responses. The findings reveal the role of ambiguity, expressed along the categories of “identity conflicts”, “role confusion” and “sensegiving void”, in processing these impulses on multiple levels. This research contributes to the emerging discourse on dynamic ambidexterity by providing implications for managers seeking to manage the dynamics of ambidexterity change in public service sector.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Case study; Dynamic ambidexterity; HEIs; Longitudinal; Theory development; Universities

Multi-level interaction effects during digital innovation activities: A case study from a digital innovation unit in the paper processing industry - Seilz, Veronika; Krause-Söhner, Elena; Schaller, Christian; Roth, Angela (BAM2023 Conference Proceedings, 2023)

Multi-sided platforms - Abdelkafi, Nizar; Raasch, Christina; Roth, Angela; Srinivasan, R (Electronic Markets, 2019)

Online-Offline Co-Creation - Daiberl, Christofer; Danzinger, Frank; Dinter, Barbara; Hess, Joseph; Höckmayr, Benedikt; Jonas, Julia; Kollwitz, C.; Luzsa, Robert; Putz, Michael; Roth, Angela; Schmitt-Rüth, Stephanie; Wehnert, Peter (2016)

Online-Offline Co-Creation für die Entwicklung neuer Dienstleistungen: Eine Anwendung im Kontext der E-Mobilität - Daiberl, Christofer; Höckmayr, Benedikt; Roth, Angela; Möslein, Kathrin (2016)

On the Way to a Systematic Service Innovation Competence Framework - Roth, Angela (The Handbook of Service Innovation, 2015)
WiSo-Import:2015-04-20:5327

On the way to a systematic service innovation framework from a competence-based perspective - Roth, Angela; Daiberl, Christofer (Cambridge Service Week, 2012)
WiSo-Import:2015-04-17:4263

Opening Embedded Systems for open Innovation - Söldner, Constantin; Roth, Angela; Möslein, Kathrin (Pacific Asia Conference on Information Systems (PACIS 2015), 2015)

Open Innovation by opening embedded systems - Söldner, Constantin; Danzinger, Frank; Roth, Angela; Möslein, Kathrin (GeNeMe 2012, 2012)
WiSo-Import:2015-04-17:4265

Open Innovation for Innovation Tools: the Case of Co-Design Platforms - Fritzsche, Albrecht; Roth, Angela; Möslein, Kathrin (Proceedings of the International Symposium on Open Collaboration, 2015)

Open Service Design? Exploring Customer Co-Creation in a Service Manufactory - Jonas, Julia; Roth, Angela; Möslein, Kathrin (ServDes Lancaster, 2014)
WiSo-Import:2015-04-17:5311

Organisational Competence for Servitization: Challenges and Determinants - Posselt, Tim; Roth, Angela; Fuhrmann, Oliver; Danzinger, Frank (The Spring Servitization Conference 2015, 2015)

Organizational ambidexterity from a process-oriented perspective: A systematic literature review - Krause, Elena; Roth, Angela; Schaller, Christian (European Academy of Management (EURAM) Annual Conference 2020 (Dublin, Ireland), 2020)
Keywords: process; ambidexterity; review

Organizational Competence for Servitization in Wholesaling - Posselt, Tim; Roth, Angela (EURAM Conference, 2015)

Partner-spreading Long Distance Traffic Networks - Bauer, Angela (International Workshop on Distribution Logistics, 2002)

Partnerübergreifende Fernverkehrsnetzwerke - Roth, Angela (Industrie-Management : Zeitschrift für industrielle Geschäftsprozesse, 2002)

Passive integration or mutual co-creation? Exploring the role of stakeholders in service innovation - Jonas, Julia; Möslein, Kathrin; Roth, Angela (QUIS 13, 2013)
WiSo-Import:2015-04-17:4948

Pesquisando a Indústria 4.0: Oportunidades e Desafios - Oks, Sascha Julian; Roth, Angela (EnANPAD 2023, 2023)

Physical interaction platforms: A taxonomy of spaces for interactive value creation - Perez Mengual, Maximilian; Danzinger, Frank; Roth, Angela (Creativity and Innovation Management, 2023)
Physical interaction platforms (PIPs) such as living labs, innovation hubs and fab labs can play a key role for complex innovation tasks in the context of grand challenges. Although research focuses predominantly on aspects like collaboration within and organization of these spaces, little research has shed light on the development process of the PIP itself. This paper aims to contribute to innovation literature by identifying essential dimensions for the design and sustainable operation of PIPs. We use and transfer conceptual knowledge and empirical evidence in an iterative taxonomy development process. Five iterations were performed: (1) initial screening of PIPs, (2) an expert workshop, systematic literature reviews on (3) platform classifications and (4) on platform-mediated value creation, and (5) a taxonomy evaluation by practitioners. The resulting PIP taxonomy consists of 18 design dimensions summarized in five groups: physical architecture, platform actors, key-value propositions, value creation and revenue logic. It contributes with (1) a tangible framework for PIP concept development building on established design dimensions from platform-, business model- and value creation literature. (2) It emphasizes criteria that require thorough reflection in the design phase (e.g., IP rights), enabling practitioners to identify and overcome critical issues early.
CRIS-Team Scopus Importer:2023-06-02
Keywords: innovation; innovation labs; living labs; platform; taxonomy

Piloting in Open Innovation Labs – A Challenge for Local Ecosystems - Roth, Angela (Innovating in the Open Lab, 2020)

Potentiale von Servicerobotern am Point of Sale - Meyer, Patrick; Roth, Angela; Gutknecht, Klaus; Möslein, Kathrin (Robotik in der Wirtschaftsinformatik, 2023)
Aufgrund steigender Online-Konkurrenz, zunehmenden Kostendrucks und omnikanaler Customer Journeys versucht der stationäre Handel durch den Einsatz innovativer Technologien neue Mehrwerte für Kunden zu bieten. In diesem Zusammenhang wird der Einsatz von Servicerobotern am Point of Sale (POS) ebenso kontrovers wie erwartungsvoll diskutiert, die Akzeptanz der Kunden ist dabei eine entscheidende Voraussetzung. Studienergebnisse zeigen, dass der unmittelbar wahrgenommene Nutzen des Serviceroboters für die langfristige Nutzungsabsicht entscheidend ist. Während sich die wissenschaftliche Forschung bislang überwiegend darauf konzentriert, die Haltung von Kunden und Verkaufsmitarbeitern gegenüber Servicerobotern zu verstehen oder einzelne Anwendungsfälle von Servicerobotern zu validieren, bleibt für einen zielgerichteten Einsatz von Servicerobotern offen, für welche expliziten Tätigkeiten Serviceroboter am POS geeignet erscheinen. Im Rahmen einer explorativen Interviewstudie wurden zwölf Handelsexperten und zwölf Experten aus dem Bereich Servicerobotik zu Einsatzmöglichkeiten von Servicerobotern am Point of Sale befragt. In Anlehnung an die Task-Technology-Fit-Theorie wurden relevante Tätigkeiten und Fähigkeiten von Frontstage-Mitarbeitern mit den gängigen technischen Leistungsmerkmalen von am Markt erhältlichen Servicerobotern abgeglichen und deren Relevanz für das Verkaufsgespräch gewichtet. Die Ergebnisse des Abgleichs wurden entlang der fünf Phasen eines Verkaufsgesprächs strukturiert. Basierend darauf wurden die Erkenntnisse in eine Weboberfläche überführt, welche Wissenschaftler und Praktiker für eine erste schnelle Indikation über die Einsatzmöglichkeiten von Servicerobotern am POS nutzen können.<br

Preface - Fritzsche, Albrecht; Jonas, Julia; Roth, Angela; Möslein, Kathrin (Innovating in the Open Lab, 2020)

Produzenten als Dienstleister: Auf dem Weg zu interaktiven hybriden Wertschöfpungssystemen - Roth, Angela; Möslein, Kathrin (Enterprise-Integration - Auf dem Weg zum kollaborativen Unternehmen, 2014)
WiSo-Import:2015-04-20:5325

Project CODIFeY: Community-based Service Innovation for E-Mobility - Daiberl, Christofer; Roth, Angela; Höckmayr, Benedikt; Möslein, Kathrin (XXVI ISPIM Innovation Conference, 2015)

Proposing the NSPIRE Technique: Improving Productivity of Networked Service Delivery - Daiberl, Christofer; Naik, Hari Suman; Roth, Angela (R&D Management Conference, 2018)

Service-Orientierung im Mittelstand - Hofmann, Bettina; Posselt, Tim; Fuhrmann, Oliver; Roth, Angela (2012)

Service robots in organisational frontlines-A retail managers' perspective - Meyer, Patrick; Roth, Angela; Gutknecht, Klaus (Journal of Retailing and Consumer Services, 2023)
Service robots (SR) have the potential to revitalise value creation in brick-and-mortar retailing. While both the competitive and evolving nature of the retailing industry as well as customers and FLE have obtained substantial coverage in academic literature, the managerial angle towards SR in organisational frontlines has rarely been addressed in service research. This qualitative exploratory interview study explores retail managers' perceptions of SR in organisational frontlines. Building on 28 in-depth interviews with retail managers, three dimensions of predisposing factors (impact on the functional, relational and organisational level), as well as two aggregated dimensions of managerial coping strategies (transforming FLE and work routines) were identified. Further, the findings reveal that retail managers perceive inherent difficulties in balancing the needs of customers and FLE when it comes to effective SR implementation.
Created from Fastlane, WoS look-up

SERVICE SYSTEMS ENGINEERING - Möslein, Kathrin; Roth, Angela; Heuberger, Albert (2020)

SERVICE SYSTEMS ENGINEERING - Sengewald, Timon; Höckmayr, Benedikt; Roth, Angela; Hohmann, Christoph; Danzinger, Frank; Kalb, Dominik (2020)

Service Systems Engineering Triggered by Digitalization – a Conceptual Framework - Höckmayr, Benedikt; Roth, Angela; Möslein, Kathrin (16th European Academy of Management Conference (EURAM), 2016)

Service Systems Engineering Triggered by Digitization – Evidence from German Manufacturing SMEs - Höckmayr, Benedikt; Genennig, Stefan; Roth, Angela; Möslein, Kathrin (16th European Association for Research on Services Conference (RESER), 2016)

Servitization and Digitalization as “Siamese Twins”: Concepts and Research Priorities - Satzger, Gerhard; Benz, Carina; Böhmann, Tilo; Roth, Angela (Springer International Publishing, 2022)
Across many industries we observe trends to change business models in favor of service offerings (“servitization”) as well as trends to apply digital technologies for value creation (“digitalization”). First, we perform a conceptual analysis to explain their interdependence. Second, we combine a topic modeling literature study and a qualitative expert interview approach to identify key research fields for the service and information system research communities. The work should deepen the understanding of service concepts to inform the purposeful design and application of digital technologies for service innovation along the identified research roadmap—as “high-tech meets high-touch”.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Digitalization; Service systems; Servitization; Value creation

Servitization in Germany – Establishing the context of servitization in manufacturing firms - Kurtz, Julian; Meyer, Patrick; Roth, Angela (Proceedings of the 9th International Conference on Business Servitization (ICBS 2022), 2022)
This book of abstracts summarizes the proceedings of the 9th International Conference on Business Servitization (ICBS 2022), held at Hotel Ilunion, Malaga, Spain. On this edition, the conference places a special emphasis on the focal theme: Servitization as a springboard for enhancing Sustainable manufacturin
Keywords: Servitization; Service Systems; Digital Transformation

Spaces for Value Co-Creation: The Case of “JOSEPHS® - The Service Manufactory” - Roth, Angela; Jonas, Julia; Fritzsche, Albrecht; Danzinger, Frank; Möslein, Kathrin (EURAM Conference, 2015)

Stakeholder integration for service innovation in German medium-sized enterprises - Jonas, Julia; Roth, Angela; Möslein, Kathrin (24th Annual RESER Conference, 2014)
WiSo-Import:2015-04-17:5312

Stakeholder integration for service innovation in German medium-sized enterprises - Jonas, Julia; Roth, Angela; Möslein, Kathrin (Service Science, 2016)

Stakeholder Integration in Service Innovation - An Explorative Case Study on Health Care Solutions Development - Jonas, Julia; Roth, Angela (EURAM Valencia, 2014)
WiSo-Import:2015-04-17:5313

Stakeholder integration in service innovation - An exploratory case study in the healthcare industry - Jonas, Julia; Roth, Angela (International Journal of Technology Management, 2017)
This paper explores the integration of internal and external stakeholders in service innovation. Building upon the co-creative paradigm, the resource and knowledge integration of stakeholders in dynamic and complex service systems is gaining importance. This case study analyses the practice of stakeholder integration in a service innovation project at a German provider for medical appliances. We show that stakeholder integration is realised in the modes of reactive integration for the majority of stakeholders, whereas mutual integration is realised with members of the organisation, only. Customers are integrated as reactive resources throughout the innovation process, also informally and indirectly. The evidence from this empirical study suggests that stakeholder integration in service systems creates interdependencies between stakeholders and implicates that indirect ways of stakeholder integration have to be taken into account for project and stakeholder management.
Created from Fastlane, Scopus look-up
Keywords: Case study research; Healthcare industry; Indirect integration; Modes of integration; Service innovation; Service systems; Stakeholder integration

Strategic ambidexterity development in a public service context: Changing the focus on short-term improvements and long-term innovation in a multi-campus university. - Krause, Elena; Roth, Angela; Schaller, Christian (European Academy of Management (EURAM) Annual Conference 2019, 2019)

Structuring the servitization journey – A socio-technical methodology for developing platform-based smart PSS - Kurtz, Julian; Meyer, Patrick; Lugmair, Nina; Roth, Angela (Proceedings of the 10th International Conference on Business Servitization (ICBS 2023), 2023)

Successful management of diverse corporate innovation communities - Roth, Angela; Dumbach, Martin; Schliffka, Barbara; Möslein, Kathrin (Journal of Strategy and Management, 2017)

Supra-adaptive Netzgestaltung durch Multi-User- Center (MUC) – Erfolgsversprechen und Potenzial - Roth, Angela (Neue Wege in der Automobillogistik: Die Vision der Supra-Adaptivität, 2007)
WiSo-Import:2015-04-20:2031

Systematic Service Development: Exploring the Role of the Setting - Fritzsche, Albrecht; Jonas, Julia; Möslein, Kathrin; Roth, Angela (R&D Management Conference, 2014)
WiSo-Import:2015-04-17:5315

Technology as a service enabler in retail environments. - Wolpert, Stefan; Roth, Angela (26th Annual Reser Conference, 2016)
The brick and mortar retail environment is currently under transition due to potential new technological innovations. The purpose of this paper is to classify and organize the accumulated knowledge about technology based retail services (TBRS) as revealed in the scientific literature. This paper presents a systematic and comprehensive review of major literature on TBRS. This study was conducted in Elsevier Scopus and led to a sample of 67 peer-reviewed articles published between 2003 and 2016 worldwide. Altogether, 32 different TBRS were identified. As far as the authors are aware, this paper provides the first systematic review of TBRS literature, which not only helps to organize retail based services but also identifies seven basic technologies underlying current TBRS.

The integration of digital technologies into service systems - Genennig, Stefan; Roth, Angela; Möslein, Kathrin (R&D Management Conference (RADMA), 2017)

The Practice of Distribution Network Planning: Coping with Shortcomings in Import Data Quality - Bauer, Angela (Sixth International Workshop on Distribution Logistics, 2001)

Towards a model of ambidexterity change: A multi-level case study in a German multi-campus university - Krause, Elena; Roth, Angela; Schaller, Christian (BAM British Academy of Management Conference 2019, 2019)
Keywords: exploitation; exploration; dynamic; longitudinal; multi-level

Towards Open Innovation in Embedded Systems - Söldner, Constantin; Roth, Angela; Danzinger, Frank; Möslein, Kathrin (AMCIS 2013, 2013)
By opening up a technology, firms can incorporate external actors to improve their products or to develop new applications on top of it. This phenomenon is discussed in the literature as open innovation (Chesbrough, 2003). An embedded system is an example of a modular and traditionally closed technology where parts of the system can be opened in order to stimulate innovation. In this paper, we want to explore how firms can pursue the opening of their embedded systems and their organization in order to unleash the potential of open innovation. By conducting twelve explorative interviews with experts in the field of embedded systems, we discovered three different forms of embedded systems openness and explored technical, internal and external organizational challenges associated with these three forms of openness. © (2013) by the AIS/ICIS Administrative Office All rights reserved.
WiSo-Import:2015-04-17:4949
Keywords: Embedded systems; Open innovation; Open technologies

Towards Perceived Service Interaction Productivity: A Proposed Conceptual Model - Daiberl, Christofer; Roth, Angela; Möslein, Kathrin (KSS Workshop, 2016)

Understanding the Role of Data for Innovating Business Models: A System Dynamics Perspective - Förster, Matthias; Bansemir, Bastian; Roth, Angela (14th International Conference on Wirtschaftsinformatik, 2019)
Data have become a key ingredient for ICT-enabled business models. Nevertheless, there is great uncertainty among scholars and practitioners alike about how to leverage data as an essential innovation resource. This raises the question of how to design data roles to innovate business models. To answer this question and to facilitate a deeper, cause-effect-relation understanding of the interdependencies between data roles and business models, system dynamics was chosen as the approach of analysis. Within a multiple case study of five business model cases with multiple embedded units per case, the study shows that there are four recurring basic data role patterns e.g. ‘incremental improvement’ or ‘initial data boost’ and two data role characteristic patterns, describing how data roles unfold within business models e.g. ‘change in self-reinforcement’ pattern. Overall, the patterns help to visualize and articulate data usage in business models and therefore contribute to the ongoing endeavor of innovating business models. <br

Use-Case-based Innovation for Artificial Intelligence - An ontological Approach - Kirschbaum, Julius; Posselt, Tim; Roth, Angela (Thirtieth European Conference on Information Systems (ECIS 2022), 2022)
Keywords: artificial intelligence; innovation; adoption; use-case; ontology

User Experience of Creativity Support Tools – A Literature Review in a Management Context - Sengewald, Timon; Roth, Angela (15th International Conference on Wirtschaftsinformatik, 2020)
Creativity Support Tools or Creativity Support Systems are a well-studied subject in the research of computer science and information systems. Whether the User Experience of Creativity Support Tools or Creativity Support Systems has been likewise sufficiently researched, shall be examined. A systematic literature search was conducted to investigate the current state of scientific literature. This review provides a brief overview of open and superfluous research areas in the field of User Experience for the development of Creativity Support Tools for business or management purposes. A total of 19 papers were selected and coded, sorted to concepts and assigned to the various phases of the creative process. The results of the analysis have shown that there is a need for further research in this field.<br
Keywords: creativity support tools; creativity support systems; user experience

Value Creation in the Information Economy: The Triad of AI, Service, and Human Work - Roth, Angela; Benz, Carina; Wilga, Matthäus; Hottum, Peter; Langes, Barbara; Lewandowski, Tom; Nägele, Rainer; Peters, Christoph; Satzger, Gerhard (Journal of Service Management Research, 2024)
Advancements in artificial intelligence (AI), particularly generative AI (GenAI), have revolutionized the value generation in service<a href="https://unihamburgde-my.sharepoint.com/personal/christian_kurtz_uni-hamburg_de/Documents/DL2030/Phase 4/Ziel 3 - Weiterentwicklung der Schwerpunktthemen/02_Triade_Dienstleistung_KI_Arbeit/SMR Journal Article/Final Submission/Roth et al_Revised Version_Value Creation in the Information Economy.docx#_ftn1" title="">[1] as well as work processes and the work environment. However, the transformative potential of AI in the context of service and work must be guided in a way that ensures its alignment with human-centric values and economic goals. Based on an interactive panel and three workshops of service researchers and practitioners at the annual conference of the German Forum for Service Research (DF)² in September 2023, this paper highlights six fields of action. Spanning corporate strategy, processes, and technology, these six fields of action illustrate how future-oriented service research may harness the opportunities of AI for society and the economy, manage associated risks, and foster societal acceptance. They serve as a framework for discussions and initiatives in service research, raise awareness among companies about necessary changes to remain competitive, and highlight funding needs with high relevance, societal importance, and economic potentia
Keywords: Service Research Priorities; Generative AI; Future of Work; Value Creation

Value Propositions in Service Systems Enabled by Digital Technology: a Field Based Design Science Approach - Genennig, Stefan; Roth, Angela; Jonas, Julia; Möslein, Kathrin (Journal of Service Management Research, 2018)

Wechselwirkungen zwischen Transport- und Lagerströmen – Ansätze aus Praxis und Theorie, Gesellschaft für Operations Research - Bauer, Angela (Planung von Distributionsnetzwerken für Neufahrzeuge, 2003)

Wege nach oben - Blickpunkt Bildungswege - Roth, Angela (LOG.Kompass, 2010)
WiSo-Import:2015-03-26:1926